SISTEM INFORMASI PENERIMAAN DAN PENGELUARAN BARANG PADA CV.KARUNIA PRAKARSA MANDIRI - Waliadi Gunawan; Rendi Rynaldi (Journal of Innovation And Future Technology (IFTECH), 2020)
Karunia Prakarsa Mandiri is a business entity engaged in the sale of agricultural products needs (such as fertilizer materials, fertilizers, farm equipment, etc.). At the CV. Karunia Prakarsa Mandiri transactions receipts and expenditures have been made to record data on revenues and expenditures into the book of the transaction by the administration. The information system can be withdrawn designing or designing a good system, it is the operating steps in the data processing systems and procedures to support the operation of the system. And the purpose of the information system globally are bracing data processing system with the help of computers. Receipt of goods is defined as the activity of receipt of goods or materials based on receipts, expenditures are expenditures activities or materials in accordance with the list of receipt of goods from work units or departments that need. Methods of data collection in the preparation of this paper uses the method of observation, interviews, and literature. The results of this research is the application that will enhance the effectiveness of data processing and data reception determining inventory expenses in any period ahead.